HABITAÇÕES EM CONTÊINERES MARÍTIMOS: ESTUDO DE CASO - Silva, Milene; Souza, Henor (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research analyzed the thermal performance of two residences built from maritime containers, both located in Jaboticatubas, Minas Gerais, Brazil. The architectural design approach and construction materials were checked with the purpose to investigate the interferences that these choices cause on these constructions environmental quality and thermal performance, and the most common failures related to this construction typology as well. Technical inspections were made in order to diagnose the current situation and inside and outside air temperature in-site measurements were provided in different seasons (winter, spring and summer). The results showed that from the paint color, the construction implementation, up to the use of additional coverage, all result in huge differences between inside and outside environment temperature. Furthermore this constructive typology has great potential, and should be disseminated and encouraged. However, the use of thermal insulation materials and other strategies are extremely needed to improve internal thermal performance, besides qualified labor trained to work on maritime containers constructions, avoiding several problems during the work and pathologies in the future.